Dampak Propaganda PEDIGA atas Refugee Terhadap Keamanan dan Kestabilan Jerman - Welas, Ibnu Rasyid; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Islamophobia was an issue that came to be abig concern around the time the incident of 9/11and it became a concern against when there are a big wave of immigrant from Middle East,which mostly Moslem, moving towards the European country especially towards country’s thataccept refugee like Germany. The issue of big wave of migrant from moslem majority countries,that seek refuge because of war, famine etc, trigger the emergence of social organization likePEGIDA that have certain hatred toward moslem refugee in German. PEGIDA itself inprevious research and recent article, it was explained that they show their hate toward them(Moslem refugee) without hiding it. This is the result of their fear toward big changes that mayor may not happen toward German that have different believes and religions. The result of thisresearch shows the impact of PEGIDA’s rejection and hate towards Moslem refugee towardgerman’s security and stability which is pretty significant. The impact of action and believesfrom PEGIDA towards Moslem refugee in German itself influence social, culture and economicvalues in German.